Dissolving uptake-hindering surface defects in metal-organic frameworks - Mueller, Kai; Vankova, Nina; Schoettner, Ludger; Heine, Thomas; Heinke, Lars (Chemical Science, 2019)
Metal-organic frameworks (MOFs) have unique properties which make them perfectly suited for various adsorption and separation applications; however, their uses and efficiencies are often hindered by their limited stability. When most MOFs are exposed to water or humid air, the MOF structure, in particular at the surface, is destroyed, creating surface defects. These surface defects are surface barriers which tremendously hinder the uptake and release of guest molecules and, thus, massively decrease the performance in any application of MOFs. Here, the destruction by exposure to water vapor is investigated by using well-defined MOF films of type HKUST-1 as a model system for uptake experiments with different-sized probe molecules as well as for spectroscopic investigations, complemented by density functional theory calculations of the defect structure. In addition to the characterization of the surface defects, it is found that the pristine MOF structure can be regenerated. We show that the surface defects can be dissolved by exposure to the synthesis solvent, here ethanol, enabling fast uptake and release of guest molecules. These findings show that the storage of MOF materials in a synthesis solvent results in healing of surface defects and enables ideal performance of MOF materials.
CRIS-Team Scopus Importer:2022-04-14